Obituary : Jan Frits Veldkamp (1941–2017) - Baas, Pieter; Hovenkamp, Peter (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2018)
An obituary for Jan Frits Veldkamp who passed away on 12 November 2017